Silver/Gold Core-Shell Nanoprism-Based Plasmonic Nanoprobes for Highly Sensitive and Selective Detection of Hydrogen Sulfide - Yang, Xinjian; Ren, Yuqian; Gao, Zhiqiang (Chemistry : a European journal, 2015)
A simple and highly sensitive and selective hydrogen sulfide assay utilizing plasmonic nanoprobes is presented in this report. The assay employs the etching of silver in the Ag/Au core–shell nanoprisms, accompanied by surface plasmon resonance (SPR) signal depression and shift. Briefly, thin layers of gold are first coated onto silver nanoprisms. The thin gold layer not only guarantees the high stability of the plasmonic nanoprobes but also ensures the high selectivity toward hydrogen sulfide. Once hydrogen sulfide is introduced, the silver core is converted to Ag2S mainly from its lateral walls. Moreover, the SPR peak is located in the NIR region that makes these plasmonic nanoprobes more appealing for the detection of hydrogen sulfide in real‐world samples and in in vivo applications. Plasmonic nanoprobes: Plasmonic Ag/Au core–shell nanoprism nanoprobes are demonstrated for the detection of hydrogen sulfide based on the strong ability of hydrogen sulfide to etch the Ag/Au core–shell nanoprisms. In the presence of hydrogen sulfide, silver in the nanoprisms is converted to Ag2S at the defective lateral walls, accompanied by an obvious surface plasmon resonance (SPR) absorption depression and peak shift (see figure).